(untitled) (De Musica, 2023)
How can sound and space be connected not only in a metaphorical sense? Over the last decades, philosophy of sound, aesthetics, and musicology have shown increasing interest in space inquiry. However, the way we interact with each other, communicate in space, and gather information about/in space is rooted in sound in a completely different way from those of musical metaphors. In this paper, I present an analysis of the role sound plays in the constitution of both space and relations of intimacy within it. Starting from the wealthy tips that E. T. Hall gives to us in order to delineate a new understanding of proxemics that includes sound experience, I argue that sound, silence, and noise are essential to determine the intimate space and the way we interact with it. Moving from a classical proxemics perspective, the analysis will focus on the intimate relation between sound, space, and body, dialoguing with phenomenology, anthropology, semiotics, and philosophy of space.